IDEAS TO FACILITATE THE GROWTH OF TEACHER EDUCATION FOR THE TIME BEING (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article contains a conclusion about that a complex of three  interrelated components: modern content that is transmitted to students, active  teaching methods and monitoring of educational results, as well as the availability  of modern infrastructure to ensure the learning process – allows students to master  technologies for teaching literature in modern school.